Computer Based Test In Modern Era For Students At Mitradharma Senior High School - Urip Ripana (Glosains: Jurnal Sains Global Indonesia, 2022)
Test is an assessment tool in written form to record or observe student achievement in line with the assessment target (Jacobs & Chase, 1992; Alwasilah, 1996). The answers expected in the test according to Sudjana and Ibrahim (2001) can be written, verbal, or deed. However , the media for the test also affects students ' success in the test . The test activities used in various schools are still conventional, namely only with paper media which has some weaknesses in the process, although in the current era it will be easier and more efficient if the test activities are computer-based or we call CBT (Computer Based Test). Computer Based Test is an exam that is done on a computer so it does not require paper, pen or pencil to answer the questions. According to (S. Al-Amri, 2008: 22-44) Currently, the use of computer-based testing is quite widespread in the corporate world. Therefore CBT ( Computer Based Test ) is the best option in mid test and final exam . This research focused the test on computer media and then the researcher get the results with PBT to know the effectiveness. The writer used approaching method. The data of the research contain 143 participants including 133 students and 10 teachers who use the test with computers media. The results of research have given writer found if those students are interested in CBT other than FBT because it’s easier and it can be solve on time. Beside the data of students the writer have others data from teachers who agree if CBT is acceptable and help teachers to check the results of the test.